Elp3‐mediated codon‐dependent translation promotes mTORC2 activation and regulates macrophage polarization. (3rd August 2022) - Chen, Dawei; Nemazanyy, Ivan; Peulen, Olivier; Shostak, Kateryna; Xu, Xinyi; Tang, Seng Chuan; Wathieu, Caroline; Turchetto, Silvia; Tielens, Sylvia; Nguyen, Laurent; Close, Pierre; Desmet, Christophe; et al.
Abstract: Macrophage polarization is a process whereby macrophages acquire distinct effector states (M1 or M2) to carry out multiple and sometimes opposite functions. We show here that translational reprogramming occurs during macrophage polarization and that this relies on the Elongator complex subunit Elp3, an enzyme that modifies the wobble uridine base U34 in cytosolic tRNAs. Elp3 expression is downregulated by classical M1‐activating signals in myeloid cells, where it limits the production of pro‐inflammatory cytokines via FoxO1 phosphorylation, and attenuates experimental colitis in mice. In contrast, alternative M2‐activating signals upregulate Elp3 expression through a PI3K‐ and STAT6‐dependent signaling pathway. The metabolic reprogramming linked to M2 macrophage polarization relies on Elp3 and the translation of multiple candidates, including the mitochondrial ribosome large subunit proteins Mrpl3, Mrpl13, and Mrpl47. By promoting translation of its activator Ric8b in a codon‐dependent manner, Elp3 also regulates mTORC2 activation. Elp3 expression in myeloid cells further promotes Wnt‐driven tumor initiation in the intestine by maintaining a pool of tumor‐associated macrophages exhibiting M2 features. Collectively, our data establish a functional link between tRNA modifications, mTORC2 activation, and macrophage polarization. Synopsis: Translational reprogramming occurs during macrophage polarization and involves tRNA modifications. The tRNA‐modifying enzyme Elp3 limits M1 but favors M2 macrophage polarization by promoting the translation of the mTORC2 regulator Ric8b in a codon‐dependent manner. Elp3 expression is downregulated by LPS/IFNγ but induced by IL‐4/IL13 Elp3 deficiency exacerbates colitis and blocks M2 macrophage polarization in mice Elp3 regulates mTORC2 activation by promoting Ric8b mRNA translation in a codon‐dependent manner. Metabolic reprogramming linked to M2 macrophage polarization requires Elp3‐mediated production of mitochondrial ribosome large subunit proteins Mrpl3, Mrpl13, and Mrpl47. Abstract : The catalytic subunit of the Elongator complex, Elp3, differentially regulates macrophage polarization by promoting the translation of the mTORC2 regulator Ric8b.